PENERAPAN APLIKASI SISTEM INFORMASI MANAJEMEN ARSIP PLUS (SIMARS PLUS) DI BADAN PERPUSTAKAAN DAN ARSIP PROVINSI DKI JAKARTA - , ANA ISWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This report of final project explains about Implementation of Plus Archives Management Information System (SIMARS Plus) Application in BPAD Provinsi DKI Jakarta. Application of SIMARS Plus is archives management application which developed by core RECMAP. It is based on desktop which used as back end and based on website which used as front end. Writing of final project used four methods. First method is observation which was sightseeing, survey and direct participation by Fieldwork Practices in BPAD Provinsi DKI Jakarta. Secondly, the method of interview with employees which correspond and competence in implementation of SIMARS Plus Application, process of digitalization and service of achives. Thirdly, documentary studies which explored information from the publication archives of BPAD Provinsi DKI Jakarta. Lastly, collecting data by literature review which compatible with theme of final project. Conclusion of this final project is implementation of SIMARS Plus apllication in BPAD Provinsi DKI Jakarta has not optimal yet which based on digitalization activities and development of data center as center of data with the step of digitalization cover: preparation, implementation digitalization and migration of data. It caused by application still in development step and limited human resources. Meanwhile, availability of facilities in BPAD Provinsi DKI Jakarta completely enough.